Analisis Niat Pembelian Item Game Mobile Legend Ditinjau dari Perspektif Motivasi dan Impulsivitas Mahasiswa Akuntansi - Amin Wijoyo; Ferry Adang; Arifuddin Arifuddin; Asri Usman (Akuntansi, 2026)
The global gaming industry has grown rapidly, encouraging the use of microtransactions for virtual items in mobile games such as Mobile Legends, especially among university students. This study focuses on accounting students who may purchase in-game items either intentionally or impulsively. It aims to examine the influence of purchase motivation, impulsive behavior, social norms, and perceived behavioral control on students’ purchase intentions. The research is grounded in the Theory of Planned Behavior (TPB) and consumer behavior theory, supported by prior studies emphasizing consumption value, hedonic motivation, and impulsiveness in digital purchasing. Using a quantitative approach, the study collects data from 100 accounting students in Jakarta through Likert-scale questionnaires and analyzes it using Structural Equation Modeling (SEM) with AMOS. The results are expected to show that all examined factors positively influence purchase intention. This research contributes to the understanding of digital consumer behavior and highlights the importance of financial literacy, as impulsive spending on virtual items relates closely to personal financial management. It also aligns with the digital economy and financial behavior research focus of Universitas Tarumanagara.